Relationship between pelvic floor muscle function and insulin resistance among non-diabetic females: a 3d ultrasound evaluation - Lei Wang; Yunyun Cao; Ping Li; Ping He; Ping Chen (Journal of Obstetrics and Gynaecology)
Background To use the three-dimensional (3D) ultrasound for assessment of pelvic floor muscle function in non-diabetic females with insulin resistance (IR), and to evaluate its functional relationship with insulin levels.Methods From October 2022 to November 2023, 216 non-diabetic females with insulin-resistant (IR group) and 118 normal females (control group) were sequentially recruited from our hospital for our study. The 3D ultrasound was used to assess the levator hiatus in resting state for all females regarding diameter lines, perimeters and areas; as well as the Valsalva manoeuvre (VM). The t-test and linear regression model were used to analyse the collected data.Results The analysis indicates that there were significant differences in the resting state of the levator hiatus between the IR and the control groups (14.8 ± 5.8 cm2 and 11.6 ± 2.7 cm2, p < 0.05); and in the VM (18.2 ± 6.3 cm2 and 13.4 ± 3. 4 cm2, p < 0.05). In addition, the anterior-posterior (AP) diameters of the hiatus on VM were significantly increased in the IR group (40.0 ± 4.7 mm and 33.0 ± 4.4 mm, p < 0.05). With insulin levels as the dependent variable, multivariate regression analysis shows that insulin levels were significantly correlated with the levator hiatus area on VM (p < 0.05) and waist circumference (p < 0.05). The pelvic organ descent on VM in the IR group was significant (p < 0.05).Conclusions The areas of resting state levator hiatus and on VM were significantly larger in the IR than that in the control groups. In addition, the position of the pelvic organ on VM in the IR group was significantly descended. The insulin levels were correlated with the pelvic floor muscle function.